The impact of language use on multilingual santri At Luhur Malang Islamic Boarding School: Sociolinguistic study - Santuso, Ahmad (Maliki Interdisciplinary Journal, 2024)
This study aims to examine how more than one language is used by Luhur Malang students. In this study, data on how to use the language was collected, and what factors can occur in the use of more than one language. The main purpose of this research is to understand how the use of two languages occurs, what factors cause, how code switching, code mixing, and so on occur. As well as what are the influences in these matters. Twenty participants in this study were in grades B and C.